2021
DOI: 10.3390/su132212396
|View full text |Cite
|
Sign up to set email alerts
|

A Cloud-Based with Microcontroller Platforms System Designed to Educate Students within Digitalization and the Industry 4.0 Paradigm

Abstract: The primary purpose of this paper is to present a system intended for student education based on a microcontroller platform and a cloud system where data will be stored. Obtained research results will be based on the application of The NodeMcu platform for data collection with sensor systems. MatLab, ThingSpeak cloud system, and the Virtuino platform will be used for data presentation. Quantitative data are applied to determine conditions for agriculture system performance management. By analyzing the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The suggested approach was adjusted to introduce and foster communication among students about the fundamentals of machine learning, which is an essential process for many agricultural operations and are connected with other contemporary technological methods of the digital era, such as networking. It must be noted that, based on the literature review and the current state of agricultural management, it can be inferred that there are limited specialized educational courses addressing these concerns [41]. The findings presented align with and build upon previous educational discoveries in the field [63,66,86], as they fulfill the objectives of agri-food professionals involved in the shift towards sustainable agriculture.…”
Section: Educational Aspectsupporting
confidence: 73%
See 1 more Smart Citation
“…The suggested approach was adjusted to introduce and foster communication among students about the fundamentals of machine learning, which is an essential process for many agricultural operations and are connected with other contemporary technological methods of the digital era, such as networking. It must be noted that, based on the literature review and the current state of agricultural management, it can be inferred that there are limited specialized educational courses addressing these concerns [41]. The findings presented align with and build upon previous educational discoveries in the field [63,66,86], as they fulfill the objectives of agri-food professionals involved in the shift towards sustainable agriculture.…”
Section: Educational Aspectsupporting
confidence: 73%
“…Apart from the more conventional educational approaches dealing with engineering with electromechanical [39,40] and basic IoT [41] solutions applied in modern industry and agriculture, various educational projects aim to improve individuals' AI literacy. According to recent research [42], preliminary courses on AI are offered at various educational levels, from elementary school [43] and secondary education [44,45] to higher education [46,47].…”
Section: Related Work and Rationalementioning
confidence: 99%
“…Moreover, IT project management excellence enables organizations to leverage technology solutions to address sustainability challenges and opportunities. For example, the adoption of cloud computing [35], data analytics, and Internet of Things (IoT) [36,37] technologies can help organizations optimize energy consumption, improve agility, and enhance resource efficiency in their operations [38][39][40][41].…”
Section: Key Dimensions Of It Project Management Excellencementioning
confidence: 99%
“…It must be noted that, although there are studies comparing the effects of using robotics in elementary and secondary schools, there are less empirical studies on the real effect of applying robotics in higher education [55]. Furthermore, recent analysis of the literature and the situation in monitoring and managing in the agriculture and ecology field, indicated that there are few special education courses regarding these issues [71]. These remarks make the contribution of the proposed approach even more beneficial for the research community.…”
Section: Educational Impactmentioning
confidence: 99%